Attitude Towards Replacement of Missing Teeth Among the Patients Visiting Nobel Medical College and Teaching Hospital - Rathi, Ankita; Chhetri, S (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: Teeth play a significant part in the maintenance of a healthy personality and an affirmative self-image. Tooth loss is psychologically a very traumatizing and upsetting experience, and is considered to be a serious event in the life of a person, requiring significant psychological readjustment. Objective: Evaluate the prosthetic status and attitude of the patients towards replacement of the teeth among the patients visiting dental department, Noble Medical College and Teaching Hospital (NMCTH) Materials and Methods: A cross sectional study was conducted over a duration of 6 months to determine prosthetic status and attitude of the patients towards replacement of the teeth among all patients visiting Department of prosthodontics, NMCTH. The inclusion criteria was all patients with at least one missing tooth (excluding third molars) and subjects who gave consent for the study. All the Patients were provided with six close ended questionnaire followed by clinical examination by a well trained investigator. Result: The total number of participants was 297. Of them 157 were male and 140 were female. Most frequently encountered age group was 21-30 years Of these, 80.8% of individual were provided with proper information about replacement of teeth whereas 19.2 % were not. 70.7% individual said they will replace only when they find difficulty in their daily activities. 64.6 % of individual wanted to replace teeth for appearance, 20.5% for function and 14.8% for both appearance and function. 79.5 %stated financial problem and 18.2% stated lack of awareness regarding not replacement of teeth. Conclusion: The patients’ attitudes and demand towards the replacement of missing teeth might be different from the clinicians’ assessment. We consider factors such as the preservation of natural teeth and the maintenance of periodontal health as priority but patients tends to prioritize comfort in mastication and improvement of esthetics. Therefore, it is vital to investigate patients’ awareness, need and demand on prosthodontic treatment options.